Implementasi Reward ASYIK dalam Meningkatkan Rasa Percaya Diri Anak Kelompok A di TK Negeri Tegal Menteng Jakarta Pusat - Siti Soleha; Khusnul Khotimah; Satiyah Satiyah; Lia Ruswiyati; Sri Watini (Jurnal Syntax Admiration, 2024)
This research aims to increase self-confidence in Group A children at TK Negeri Tegal, Menteng, Jakarta Piusat, through the implementation of the "ASYIK" reward system. The research subjects were 30 children aged 4-5 years. The method used was classroom action research conducted in two cycles. Initial observations showed that the children's confidence level only reached 40%, far below the 80% target. After implementing the "ASYIK" reward, there was a significant increase from 37.5% in cycle 1 activity 1 to 80% in cycle 2 activity 2. The success of the intervention was marked by 12 out of 15 children in class A achieving the Very Well Developed (BSB) criteria. The improvement in children's self-confidence was evident, where before the intervention only 4 children had BSB scores, increasing to 5 children after cycle 1, 8 children (60%) after cycle 2 activity 1, and finally 12 children (80%) after cycle 2 activity 2. The results of this study indicate that the implementation of the "ASYIK" reward is effective in increasing self-confidence in Group A children at TK Negeri Tegal Menteng, Jakarta Pusat.